Analisis Strategi Komunikasi Digital Kementerian Pertahanan dalam Menjalankan Fungsi Media Relation melalui Website dan Media Sosial Kemhan RI - Andina Mutiara Ramadanty; Garcia Krisnando Nathanael (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Communication transformation requires agencies, including the Ministry of Defense (Kemhan RI), to maximize the use of their official websites as communication channels, especially in the context of media relations. Kemhan has unique information characteristics, namely high information sensitivity that requires a balance between transparency and information security. This study aims to analyze the Ministry of Defense's digital communication strategy in carrying out its media relations function. This study uses a descriptive qualitative method with data collection techniques of observation and interviews, as well as Miles and Huberman's data analysis technique with the help of the Nvivo 12 application. This study uses Frank Jefkins' Digital Communication and Media Relations theory. The findings of this study indicate that the Ministry of Defense utilizes both platforms as its main communication channels, with the website serving as a source of accurate official information, while social media functions as a means of disseminating interactive and wide-ranging content. This strategy is supported by the provision of accurate information, timely content adjustments, and collaboration to serve the needs of the media in line with Frank Jefkins' media relations theory. This study presents a novelty in examining the media relations practices of the Ministry of Defense, which has high information sensitivity, a new perspective from the literature dominated by other agencies that do not have limitations on public information.